Adjunctive Low-level Laser Therapy Using 980-nm Diode Laser after Impacted Mandibular Third Molar Surgery: A Randomized Clinical Trial - Sirus Risbaf-Fakoor; Hadi Hashemzehi; Hassan Jahantigh; Kimia Arab; Leila Gholami (پزشکی بالینی ابن سینا, 2020)
Background and Objective: Extraction of impacted lower third molars is one of the most frequent surgeries of the oral cavity. This operation might be accompanied by inevitable complications, such as pain, swelling, and trismus after surgery. Therefore, the aim of this study was to evaluate the impact of low-intensity/power laser therapy on swelling and trismus after impacted mandibular third molar surgery. Materials and Methods: This randomized double-blind clinical trial was performed on 40 patients who required similar unilateral impacted third molars. These patients were randomly divided into two groups of 20, including the control group with no laser application and the test group receiving laser irradiation. In the intervention group, 1 cm2 of the tissue was irradiated immediately post-operation by 12 j/cm2 energy using a 980-nm laser setting with continuous wave mode at the output power of 200 MW for 60 s. Radiations were carried out at three regions, including two intraoral sites on the buccal and lingual sides of the operated area and an extraoral area on the joining point of the masseter muscle to the mandible. Inflammation and trismus were assessed by measuring the size of the face and maximum mouth opening on the second and seventh days after surgery. Results: Our findings demonstrated that in the laser group, on the second day post-operation the maximum mouth opening (trismus) was 28±6 and facial swelling was 217.8±12.8. The two groups were not significantly different on this day regarding the two evaluated variables (P>0.05). On the seventh day, trismus and facial swelling were reported as 39.85±6.97 and 209.2±13.45, respectively. Moreover, improvements were observed in the irradiated group at this time point. However, no statistically significant difference was found between the test and control group concerning these factors (P>0.05). Conclusion: According to the results of this study, laser application with the parameters set in this study had no significant positive effects on reducing the post-operation complications.